Advanced age and liability to oxaliplatin‐induced peripheral neuropathy: post hoc analysis of a prospective study. Issue 5 (17th December 2012) - Argyriou, A. A.; Briani, C.; Cavaletti, G.; Bruna, J.; Alberti, P.; Velasco, R.; Lonardi, S.; Cortinovis, D.; Cazzaniga, M.; Campagnolo, M.; Santos, C.; Kalofonos, H. P.
Abstract : Background and purpose: The aim of this post hoc analysis of data extracted from a prospective, multicenter study is to test in a large homogenous population of chemotherapy‐naïve patients with colorectal cancer (CRC) treated with oxaliplatin (OXA)‐based chemotherapy whether advanced age increases the risk of developing OXA‐induced peripheral neuropathy (OXAIPN). Methods: One‐hundred and forty‐five patients with CRC, without other significant co‐morbidities predisposing to peripheral neuropathy, were divided according to their age into two groups: patients aged between 50 and 68 years (group I, n = 75); and patients aged ≥ 69 years (group II, n = 70). Patients were prospectively monitored at baseline and followed‐up during chemotherapy using the motor and neurosensory National Cancer Institute Common Toxicity criteria, the clinical version of the Total Neuropathy Score and neurophysiology. The incidence and severity of both the acute and cumulative OXAIPN was thoroughly determined and then compared between age groups. Results: No statistically significant difference was observed in the incidence of both the acute ( n = 64/75 vs. 56/70; P = 0.510) and cumulative OXAIPN ( n = 51/75 vs. 49/70; P = 0.858) between age groups. The severity of OXAIPN was also similar between age groups. In line with the clinical data, the neurophysiological results between age groups were also comparable. Conclusion: The results of this study indicate that advanced age does not seem to represent a significant risk factor of OXAIPN in patients with CRC without any other significant co‐morbidities.